Lippia agrestis (Verbenaceae): a new species from the northern Bahia state, Brazilian Caatinga - Lima, Maria Tânia Correia; Salimena, Fátima Regina Gonçalves; Cardoso, Pedro Henrique; Conceição, Adilva De Souza (Phytotaxa, 2026)
Based on fieldwork and examination of Lantaneae herbarium collections, Lippia agrestis is here described as a new species. It is characterized by the unique combination of the following traits: leaves with margin entire near the base and conspicuously serrate towards the apex, spikes with peduncles 0.7‒1.5 cm long, basal bracts 0.5‒0.7 × 0.3‒0.4 cm, ovate, internal bracts 0.5‒0.6 × 0.2‒0.3 cm, lanceolate, corolla tubes 1‒1.2 cm long, well surpassing the bracts in length, externally densely pubescent-glandulous, densely sericeous ovary, and drupaceous fruits with a strigose dorsal surface. The species is found in the Raso da Catarina Ecoregion, within the Caatinga domain (Bahia state, Brazil). It grows in sandy, bushy caatinga, at elevations between 405 and 430 m. Illustrations, a distribution map, and comparisons with similar species (Lippia carrascoana, Lantana restingensis, Lippia maximilianii) are provided. A preliminary conservation status assessment suggests that Lippia agrestis qualifies as Endangered (EN).